(untitled) (Al-Academy, 2023)
Advertising is an important and influential tool in various commercial operations, as it represents a means of communication that depends on influencing individuals or society as a whole, working on a link between the producer and the consumer, so the importance of advertising appears in two dimensions, the first is economic represented in its role in achieving economic growth for the facility, while the social dimension lies in its role By influencing the behaviors and ideas of individuals, and from here it appears to us the importance of formulating, organizing and designing the advertising message that advertising agencies resort to in their advertising campaigns. Orientation, definition, and raising the level of the advertising message for local products and their acquisition?While the goal of the research was determined in revealing the visual appeal and its reflections in advertising design, and the theoretical framework was concerned with two sections, the first topic touched on the characteristics of visual appeal and the formation of discourse, while the second topic touched on the visual appeal in commercial advertising, and in the third chapter, two research models were described and analyzed , based on the paragraphs of analysis deduced from the theoretical framework, and the resulting indicators, and included a presentation of the results reached by the researcher, including:- Relying on the characteristics of advertising organization by stimulating desires and arguing with the subconscious mind to entice it to the recipient, so that the characteristic of suspense is present and develops motivation.- Focusing on the brand and its color value in all samples to show the identity of the product, its characteristics and advertising characteristics, with the possession of that visual identity, the visual appeal in which is an attractive and interesting appeal that achieves attention and excitement in all samples.